PENGARUH SUKU BUNGA SBI, INFLASI, KURS DAN VOLUME PERDAGANGAN SAHAM TERHADAP HARGA SAHAM (Studi Kasus Perusahaan Food and Beverages Yang Terdaftar Di BEI Tahun 2018-2020) - Eni Indriani; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the influence of SBI interest rates, inflation, exchange rates, and stock trading volumes on the share prices of food and beverages companies in 2018-2020. The sample in this study was 20 corporate that were food and beverages companies. The sampling technique used is purposive sampling. The data used in the study used secondary data. The data analysis method is multiple linear regression tests. The research results show simultaneously that each variable of SBI interest rate, inflation, exchange rate, and stock trading volume affect the stock price. Partially, the SBI interest rate and stock trading volume positively affect the stock price. Meanwhile, the exchange rate and inflation partially do not affect the share price of food and beverage companies.Keywords:    SBI Interest Rate, Inflation, Exchange Rate, Stock Trading Volume, Stock Price